HUBUNGAN PENGGUNAAN PESTISIDA DENGAN KEJADIAN HIPERTENSI PADA PETANI PADI DI DESA GRINGSING KECAMATAN GRINGSING KABUPATEN BATANG - Marda Louisa; Sulistyani Sulistyani; Tri Joko (Jurnal Kesehatan Masyarakat (Undip), 2018)
Background: Pesticides are chemical compounds or chemical compound mixtures that have the ability to eradicate and kill pests. The use of poorly managed pesticides will have a negative impact. The effects of these pesticides can be acute and chronic. Pesticide poisoning can cause hypertension. Gringsing Village, Gringsing District, Batang District has hypertension cases of 1,742 cases. Aim : knowing the association between pesticide use and hypertension incidence on rice farmers in Gringisng Village, Gringsing Sub-district, Batang DistrictMethod: This study used cross sectional design with 78 respondents. The variables studied were age, sex, history of disease, length of service, duration of work, dose of pesticide, spraying frequency, spraying time, Personal Protective Equipment (PPE), activity, genetic, eating and smoking habitResult : showed that the variables that gave significant results were: Age (p = 0.025), gender (p = 0.014), length of service (p = 0.017), Personal Protective Equipment (p = 0,015), genetic (p = 0,035), and smoking (p = 0.017).Conclusion : Age, sex, length of service, personal protective equipment, genetics and smoking have a relationship with the incidence of hypertensionSuggestion: the need to improve farmers' practices in using pesticides